Biological Nitrification Inhibition (BNI): Phenotyping of a core germplasm collection of the tropical forage grass Megathyrsus maximus under greenhouse conditions - CGIAR Research Program on Livestock (2020)
A group of accessions (cluster) with the most desirable agronomic and environmental traits was identified for further field validation. The results demonstrate the ability of M. maximus to suppress soil nitrification and N2O emissions, potentially contributing to the development of improved N-conserving forage grasses for tropical livestock production.